L1 Japanese Perceptual Drift in Late Learners of L2 English - Chikako Takahashi (Languages, 2024)
This study presents evidence of second language (L2) influence on first language (L1) perception of alveolar stops. Sixty-one L1 Japanese late learners of L2 English (onset ~12 years old) in Japan (N = 31) and in the US (N = 30) participated. We examined late L2 learners’ L2 perceptual ability and L1 perception drift by administering three perception tasks (AX discrimination, forced categorization, and goodness rating) on word-initial stop consonants. The L2 learners’ L1 Japanese and L2 English data were compared to those of Japanese and English monolinguals, respectively (N = 21, N = 16). All participants’ production data were also gathered to examine potential perception-production relationships. Late learners’ sensitivity patterns along a synthesized /da–ta/ continuum differed significantly from those of monolingual speakers, with a sensitivity peak location between the monolingual Japanese and English groups. This suggests that late learners’ voicing category boundaries may have been influenced by L2 English learning. The L2 learners’ goodness rating patterns of L1 Japanese stimuli also showed evidence of L1 perceptual drift: L2 learners tended to be more accepting of Japanese stimuli with longer VOTs compared to Japanese monolinguals.